A Simple Model of Foreign Brand Penetration under Monopolistic Competition - Toru Kikuchi (Economics and Econometrics Research Institute (EERI), 2009)
The main purpose of this study is to illustrate, with a simple monopolistic competition trade model, how trade liberalization (i.e., a decline in trade costs) can affect domestic entrepreneurs' decisions between domestic brands and foreign brands, and thus the degree of foreign brand penetration. It is shown that, as trade costs decrease, more entrepreneurs choose to provide foreign brands. However, the impact of trade liberalization (in terms of changes in profit levels) becomes smaller as more entrepreneurs switch to foreign brands.
Keywords: F12; 330; Foreign brand penetration; trade liberalization; monopolistic competition